CHARACTERISTICS OF ADULT PULMONARY TUBERCULOSIS PATIENTS UNDERGOING HOSPITALIZATION AT SONDOSIA REGIONAL HOSPITAL, BIMA REGENCY PERIOD JANUARY - JUNE 2023 - Rizky Taufika, Amandha (Journal of Advance Research in Applied Science (ISSN 2208-2352), 2023)
Pulmonary tuberculosis (TBC) is a disease caused by an aerobic germ, Mycobacterium tuberculosis, which can live mainly in the lungs and various other organs of the body. The type of research is quantitative descriptive. The population in this study was 53 patients of Pulmonary TBC patients who underwent hospitalization at Sondosia Hospital. Sampling in this study used a total sampling technique where the study used the entire population into a research sample, so that the number of samples in this study was 53 people. This research was conducted at Sondosia Hospital, Bima Regency in January - June 2023. The results of this study showed that patients with the most gender were male 66% and female 34%. Based on age, the most age category is the age of >60 years, which is 43.3%,. Based on education, the highest level of education is elementary school level 34%. Based on occupacy, the largest category was working as a farmer 35.8%. Symptoms of TBC disease experienced by patients, most experienced cough as much as 100%, those who experienced shortness of breath was 56.6%, patients who experienced fever was 17%, who experienced night sweats 22.6% while those who experienced weight loss was 11.3%. Based on disease status,it was found that 75.5% new cases, 13.2% dropped out and 11.3% relapsed. Based on comorbidities, type 2 diabetes mellitus was 13.2% and hypertension 11.3%. Based on smoking history, patients with a history of smoking as much as 50.9%. Based on the most nutritional status with normal nutritional status 79.2%.